Optimizing antifungal prophylaxis in allogeneic stem cell transplantation: A cohort study of two different approaches. Issue 6 (15th November 2022) - Selby, Philip R.; Warner, Morgyn S.; Peake, Sandra L.; Bardy, Peter; Hiwase, Devendra; Singhal, Deepak; Beligaswatte, Ashanka; Hahn, Uwe; Roberts, Jason A.; Yeung, David; Shakib, Sepehr
Abstract: Background: Limited consensus exists on the optimal use of antifungal agents to prevent invasive fungal infection in the early post allogeneic hematopoietic stem cell transplant (alloHCT) period, particularly when patients cannot tolerate oral medication administration. Methods: We undertook a retrospective observational cohort study to assess the tolerability, efficacy, and cost of a new antifungal prophylaxis pathway at a major tertiary alloHCT centre. Patients aged ≥16 years who underwent alloHCT between February 2018 and October 2019 (cohort 1) or between April 2020 and November 2021 (cohort 2) were included. In both cohorts, first line prophylactic therapy was oral posaconazole. The second line drugs where oral therapy was unable to be administered were intravenous voriconazole (cohort 1) versus intravenous posaconazole (cohort 2). Results: There were 142 patients enrolled in the study, 71 in each cohort. The proportion of patients remaining on first‐line prophylaxis or progressing to second‐, third‐, and fourth‐line options was 22.5%, 39.4%, 29.6%, and 8.5% in cohort 1 and 39.4%, 59.2%, 1.4%, and 0% in cohort 2, respectively. The frequency of neuropsychiatric adverse events was significantly higher in cohort 1 compared to cohort 2 (49.3% vs. 19.8%, p  = .0004). Occurrence of proven and probable fungal infections was not significantly different between cohorts. Antifungal drug expenditure was $359 935 (AUD) more in cohort 1 ($830 486 AUD) compared to cohort 2 ($477 149 AUD). Conclusion: The antifungal prophylaxis pathway used in cohort 2 resulted in reduced antifungal‐associated adverse effects, less patients requiring progression to 3rd and 4th line prophylaxis and reduced antifungal drug costs. Abstract :